Оптимізація процесу онлайн навчання на платформі Open edX - Галій, А. К. (ХНУРЕ, 2024)
This work is devoted to the creation of new effective solutions and forms of organization of the educational process, adapted to today's conditions, which is extremely important and relevant in the conditions of martial law in Ukraine. The purpose of the report is to research the Open edX platform and develop customizations for the platform that will help optimize consideration of the needs of users and instructors for distance learning. In this work, the development of customization for Open edX for user registration in the program was carried out.
Keywords: онлайн навчання; Open edX